(untitled) - Stanzione, Vince (Hoboken, 2013)
The Millionaire Dropout is for anyone who wants to learn the secrets for increasing their income and their standard of living. Divided into three sections, readers will walk through the stages for taking control of their life, learning how to make more money, and learning how be smart with their successes. Everyone owes it to themselves to invest a little time and effort into increasing their standard of living and releasing the personal power that is locked up inside of us all.
Keywords: Success in business,Thành công trong kinh doanh